Entrepreneurial motivation, performance and commitment to social responsibility: a conceptual analysis on the influence of Islamic religiosity - Mohammed Adamu, Isa; Kedah, Zulkarnain; Osman-Gani, Aahad M. (2011)
Although the study of religion and its effects on social phenomena had received attention lately, most research in this area is from various religious perspectives excluding Islam. To date there is dearth of precious information regarding Islamic religiosity and its effects on entrepreneurial outcomes. In this exploratory study, a conceptual analysis of the effects of Islamic religiosity on entrepreneurial motivation, performance and commitment to social responsibility is considered. We suggested that Islamic rituals have the potential benefit of fostering the entrepreneurial outcomes considered. We recommend that religious practices be encouraged in the workplace.